Perlindungan Hukum terhadap Ketentuan Me-Review Produk dimedia Sosial - I Wayan Pertama Yasa; Ni Komang Arini Styawati Styawati; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
The era of the digital economy in Indonesia has made buying and selling transactions easier and faster to do. By using social media, consumers can channel their opinions, criticisms and suggestions on the goods/services they consume to business actors in various forms. One of them is in the form of a review (review) of goods/services products that are poured through photos and videos. However, this activity reaped pros and cons in the community, because it is considered that this activity actually tarnishes the good name. This study aims to examine the form of legal protection against the provisions for reviewing products on social media. The sources of legal materials used in this paper are the first sources of primary legal materials that have binding power, the second sources of secondary legal materials which are legal materials derived from the results of literature studies by reading books, legal journals, and articles in accordance with the issue at hand. Data were analyzed by qualitative method. This study uses a normative type of research by using a deductive reasoning approach. Legal protection for the provisions for reviewing products on social media is stated in Law Number 12 of 2005 Article 23 paragraph (2) concerning Human Rights, Article 44 paragraph (3) of the UUPK, and criminal sanctions for perpetrators are stipulated in the UUPK which can be sentenced to punishment. imprisonment and fines.